The Improvement of English Skills for Islamic Junior High School Teachers Using ESA (Engage Study Activate) Approach - Ikhrom Ikhrom; Ruswan Ruswan; Sayyidatul Fadlilah (OJS Universitas Muhammadiyah Gresik, 2018)
Language is a skill that insists approach and certain strategy to master it. ESA (Engaged-Study-Activate) is an approach used in learning foreign language based on the theory that the success of learning language is determined by the factor of involvement in learned language environment. Therefore, the ideal way of learning language is that it is done in the country in which the language is used as the first language. When it is difficult to be achieved, it needs the availability of artificial learning atmosphere that gives situation as if the students are in English speaking community. This training needed three main activities: involvement, study, and language-based activities. By using those three main activities, the program of English skill improvement for the teachers of Islamic Junior high school in Tugu and Ngaliyan District was held. The result of the study through guidance shows that participants’ English skills increased. Although it is not too significant, the improvement of their English skills proves that ESA approach was appropriate to be used to maximize participants’ learning achievement. Its less significance was caused by several factors, they are: learning activities (offline learning) was held in every Friday, at the time teachers had felt tired. The offline program was also only held once a week although they were facilitated with online learning program. Another important factor that must be considered is that the teachers had many other activities related to their Islamic social organization activity. However, they still had high motivation in joining the program. They also had a good commitment to learn English. This factor had good effect towards the learning achievement improvement although it is not too high